PENGARUH KOMBINASI JARAK TANAM DAN PUPUK KOMPOS TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) VARIETAS BIMA BREBES - Suhertin, Suhertin; Jaenudin, Amran Jaenudin; Purnomo, Dwi (Agroswagati : Jurnal Agronomi, 2022)
This study aimed to determine; (1) The Combined effect of plant spacing and compost on the growth and onion yield (Allium Ascalonicum L.) Bima Brebes varieties (2) on how many spacing and dosage of compost that can increase growth and onion yield (Allium Ascalonicum L.) Bima Brebes varieties (3) correlation between growth components and onion yield (Allium Ascalonicum L.) Bima Brebes varieties. The experiment was carried out at the Ma'had Al Zaytun Campus Agricultural Complex. The location is at an altitude of ±50 m above sea level, with latosol soil type and rainfall of 27 - 400 mm/month. This experiment used a randomized block design (RBD), which consisted of 9 combinations of plant spacing and compost application, each was repeated three times, so there were 27 experimental plots. The treatment combinations tested were : A (20 cm x 10 cm, 5 kg/ha compost), B (20 cm x 10 cm, 10 kg/ha compost), C (20 cm x 10 cm, 15 kg/ha compost), D (20 cm x 15 cm, 5 kg/ha compost), E (20 cm x 15 cm, 10 kg/ha compost), F (20 cm x 15 cm, 15 kg/ha compost), G (20 cm x 20 cm, compost 5 kg/ha), H (20 cm x 20 cm, compost 10 kg/ha), I (20 cm x 20 cm, compost 15 kg/ha). The results of the study show that: Based on the discussion that has been described, the following conclusions can be drawn: (1) The combination of spacing and compost treatment had a significant effect on plant height at 25 HST and 35 HST, number of tillers per clump aged 35 HST and 45 HST, LPT aged 25 – 35 HST, weight of fresh and dry tubers per plot, but did not affect plant height at 15 HST and 45 HST, number of leaves of all ages of observation, number of tillers aged 15 and 25 HST, root volume of all ages of observation, LPT aged 15-25 HST and 35-45 HST, fresh weight and dry weight per clump, tuber diameter and number of tubers (2) The highest dry tuber weight yield per plot occurred in the combined treatment with a spacing of 20 cm x 10 cm and a dose of compost of 5-15 tons/ha, namely 3.40 kg/slot or equivalent to 9.06 tons/ha (3) Obtained a significant correlation between plant height at 35 HST and 45 HST with dry weight per plot in medium and strong categories. However, there was no significant correlation between plant height 15 HST and 25 HST. As for the number of leaves, there was no significant correlation at all ages of observation with the weight of dry tubers per plot.